(untitled) (Journal of Bio-Science, 2011)
Context: To evaluate the anti-diabetic activity of Urtica dioica L. in type 2 diabetic model rats. Objectives: The aim of this study is to explore the effect of water extract of U. dioica on glycemic status, body weight and lipidemic status in type2 diabetic model rats Materials and Methods: The mature and fresh leaves of U. dioica was collected from the mountain range of Assam in India and the leaves extract was used at a dose of 1.25 g-kg body weight. Type2 diabetes was induced by a single intraperitoneal injection of STZ to 48 hours old pups of Long Evans. Experiments for semi-chronic effects were done with continuous feeding of aqueous extract for 14 days at a dose of 1.25 g-kg body weight type 2 diabetic male rats. Serum glucose was estimated by GOD-POD method, serum triglyceride and cholesterol by enzymatic-colorimetric methods. Results: Water extract showed significant effect on lowering fasting serum glucose levels in type 2 diabetic model rats on 14th day (14.05 ± 3.4 mmol/l in control vs 8.3 ± 1.4 mmol/l in treated group, p = 0.04). There was significant increase in the body weight of treated group in comparison to the control group (175 ± 8 g in control vs in 168 ± 9 g in treated group on 0 day, p = ns; 193 ± 26 g in control vs in 185 ± 25 g in treated group on 14th day, p=0.002]. Beneficial effect was observed in lipid although the change was not statistically significant. Conclusion: The results obtained in this study suggests that U. dioica has hypoglycemic and hypo-lipidemic activity in type 2 diabetic model rats. This may be due to the histological and functional improvement of b-cells with the consequence of improved insulinemic status. Key words: hypoglycemic; hypolipidemic; Urtica dioica; diabetes mellitus DOI: 10.3329/jbs.v17i0.7092 J. bio-sci. 17: 1-6, 2009